Glucose‐regulated protein (GRP78) is an important cell surface receptor for viral invasion, cancers, and neurological disorders. Issue 6 (15th May 2021) - Gonzalez‐Gronow, Mario; Gopal, Udhayakumar; Austin, Richard C.; Pizzo, Salvatore V.
Abstract: The 78 kDa glucose‐regulated protein (GRP78) is an endoplasmic reticulum (ER)‐resident molecular chaperone. GRP78 is a member of the 70 kDa heat shock family of proteins involved in correcting and clearing misfolded proteins in the ER. In response to cellular stress, GRP78 escapes from the ER and moves to the plasma membrane where it (a) functions as a receptor for many ligands, and (b) behaves as an autoantigen for autoantibodies that contribute to human disease and cancer. Cell surface GRP78 (csGRP78) associates with the major histocompatibility complex class I (MHC‐I), and is the port of entry for several viruses, including the predictive binding of the novel SARS‐CoV‐2. Furthermore, csGRP78 is found in association with partners as diverse as the teratocarcinoma‐derived growth factor 1 (Cripto), the melanocortin‐4 receptor (MC4R) and the DnaJ‐like protein MTJ‐1. CsGRP78 also serves as a receptor for a large variety of ligands including activated α2 ‐macroglobulin (α2 M*), plasminogen kringle 5 (K5), microplasminogen, the voltage‐dependent anion channel (VDAC), tissue factor (TF), and the prostate apoptosis response‐4 protein (Par‐4). In this review, we discuss the mechanisms involved in the translocation of GRP78 from the ER to the cell surface, and the role of secreted GRP78 and its autoantibodies in cancer and neurological disorders.